Critical Remarks on the Normative Discourse about School Heterogeneity - Wischer, Beate; Trautmann, Matthias (Swiss Journal of Educational Research, 2018)
This article aims at challenging pedagogical-normative reflexions within the current discourse on school heterogeneity. After reconstructing the underlying mode of discourse argumentation, three problems are discussed: (1) vagueness and overcomplexity of the notion of heterogeneity, resulting from child-centered pedagogy, (2) neglect of structural and functional aspects of institutionalized learning, and (3) normative-pedagogical concepts of teaching that appear oversimplified in the light of professional theory.